THE CORRELATIONS BETWEEN LANGUANGE LEARNING STRATEGIES AND READING INTEREST TOWARDS STUDENTS’ READING ACHIEVEMENT - Irmayanti Irmayanti (Universitas PGRI Palembang, 2022)
This study aimed at determining: (1) the correlations of language learning strategies; (2) the corelations of reading interest; and (3) the correlations both language learning strategies and reading interest towards the students English study program at Universitas Muhammadiyah Palembang. This study was a qualitative study using simple regression method. The respondents were 60 students at Universitas Muhammadiyah Palembang. Data collection technique in this study were questioners and documentation. Validation test in this study were construct validity and content validity, while the reliability test was Cronbach’s Alpha. Normality test, homogeneity test, and linearity test had been conducted before data were analyzed using simple and multiple regression technique. The findings showed that (1) There is no significant correlations of language learning strategies on students’ reading achievement of English study program at Universitas Muhammadiyah Palembang value of 0.582; (2) There is significant correlations of reading interest on students’ reading achievement of English study program at Universitas Muhammadiyah Palembang value of 0.029; (3) There is no significant correlations of language learning strategies and reading interest simultaneously on students’ reading achievement of English study program at Universitas Muhammadiyah Palembang value of 0.082. There is simultaneous influence between language learning strategies and reading interest with reading achievement.